2022
DOI: 10.1021/jacs.2c05312
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase η Recruits DHX9 Helicase to Promote Replication across Guanine Quadruplex Structures

Abstract: DNA polymerase η (Pol η) catalyzes accurate bypass of ultraviolet light-induced cyclobutane pyrimidine dimers, and it also functions in several other related processes, including bypassing DNA with unusual structures. Here, we performed unbiased proteome-wide profiling of Pol η-interacting proteins by using two independent approaches, i.e., proximity labeling and affinity pull-down followed by LC-MS/MS analysis. We identified several helicases, including DHX9, as novel Pol η-interacting proteins. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To further examine the roles of phase separation in stabilizing G4 structures in cells, we performed BG4-ChIPseq experiment for U2OS cells that were untreated or treated with 1.5% 1,6-HD for 2 min. 30,31 Our results from two biological replicates revealed a substantially diminished number of BG4 ChIP-seq peaks, namely, from 3507 peaks in control cells to 2269 peaks in 1,6-HD-treated cells. The majority of the peaks (58.9 and 61% in control and 1,6-HDtreated cells, respectively) are located in promoter regions (Figure 3A), which is in agreement with the previously reported results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further examine the roles of phase separation in stabilizing G4 structures in cells, we performed BG4-ChIPseq experiment for U2OS cells that were untreated or treated with 1.5% 1,6-HD for 2 min. 30,31 Our results from two biological replicates revealed a substantially diminished number of BG4 ChIP-seq peaks, namely, from 3507 peaks in control cells to 2269 peaks in 1,6-HD-treated cells. The majority of the peaks (58.9 and 61% in control and 1,6-HDtreated cells, respectively) are located in promoter regions (Figure 3A), which is in agreement with the previously reported results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…G4-ChIP sequencing was performed using the custom-purified BG4 antibody and conducted as previously described with minor modifications . DNA was fragmented following the protocol described previously . Briefly, chromatin samples were diluted in a blocking buffer containing 25 mM HEPES (pH 7.5), 10.5 mM NaCl, 110 mM KCl, 1 mM MgCl 2 , and 1% BSA and treated with RNase A.…”
Section: Methodsmentioning
confidence: 99%
“…It can be anticipated that the pathogenic RFC1 harboring hundreds to thousands of AAGGG repeats may exert a more detrimental function to disease pathogenesis. Recently, the importance of G4-resolvases and G4-unfolding ligands has been increasingly recognized for neurodegenerative disease therapy ( 66–69 ). For instance, the Cockayne Syndrome B protein and DEAH-Box helicase 9 could resolve DNA G4 structures to restore normal cellular activities ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA G4 formed in RFC1 PRE appears to elicit detrimental effects on several key biological processes, and thus may be a potential therapeutic target. It has been recently reported that proteins or helicases, such as the Cockayne Syndrome B protein and DEAH-Box helicase 9, could resolve pathogenic DNA G4 structures to restore normal cellular function 46,47 . The unprecedented high-resolution structures of G4 formed by AAGGG repeats will facilitate the discovery of helicase and small-molecule ligands to resolve the culpable G4 structure in RFC1 PRE for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%